Threat Perception in Indonesia: Time Series Analysis of Defense Doctrines Between 1991 - 2023 - Priyanto, Priyanto; Akbar, Mujaddid; Timur, Fauzia Gustarina Cempaka (Universitas Sultan Ageng Tirtayasa, 2024)
National Defense Doctrine is a teaching about the fundamental principles of national defense. Defense doctrine is very important as a guideline in administering national defense. Defense doctrine is greatly influenced by developments in the global, regional, and national strategic environment, which could potentially give rise to threats, whether military, non-military, or hybrid. Defense doctrine will continue to evolve according to developments in the strategic environment and the dynamics of these threats. How to assess the nature of threats and the basic principles in overcoming these threats, as stated in the national defense doctrine from 1991 to 2023, is certainly something important to know in order to identify the various types of threats that have emerged or will emerge in the future. The research approach used by researchers is a qualitative approach using secondary data sources in the form of documents. From the research results, it can be concluded that, first, the National Defense Doctrine has undergone changes five times, namely since 1991, 2007, 2014, 2015, and 2023. Second, there are a number of similarities and differences between existing defense doctrines. Third, the Reformation Era had a significant impact on changes to the country's defense and security system. Fourth, synergy between defense components is very important in the implementation of defense.